CENTROID-MOMENT TENSOR SOLUTIONS FOR APRIL-JUNE 1988 - Dziewonski, A; Ekstrom, G; Woodhouse, J; Zwart, G (1989)
Centroid-moment tensor solutions are presented for 172 earthquakes that occurred during the second quarter of 1988. The solutions are obtained using corrections for aspherical Earth structure. © 1989.